Penerapan Metode Casework dalam Upaya Meningkatkan Kemampuan Berkomunikasi dan Kepercayaan Diri Anak Korban Bullying - Dinda Renita Sibagariang; Fajar Utama Ritonga; Mia Aulina Lubis (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Bullying is any form of bullying or violence that is intentionally perpetrated by a stronger individual or group of people with the aim of inflicting physical, emotional, or psychological harm on others. Bullying can occur anywhere, including at school, and can be carried out by teachers, students, or adults in the school environment. Many cases of bullying today attract the attention of practitioners to intervene with victims of bullying. One of them is MR, a junior high school student who is a victim of bullying at his school. He often received treatment that indicated bullying from classmates. Through this activity, practitioners are interested in intervening with MR (client) regarding the bullying case he experienced. The purpose of this activity is to examine the causes of bullying against clients and help make behavioral changes in clients such as communication skills and increased self-confidence. The method used is casework intervention in identifying client problems. The results showed that the client became more confident when communicating with others and speaking in front of people and began to dare to defend himself if he received treatment that indicated bullying.